Cassius blue, tropical striped blue Leptotes cassius (Cramer) (Instecta: Lepidoptera: Lycaenidae: Polyommatinae) - Donald W. Hall; Jerry F. Butler (EDIS)
EENY-460, a 5-page illustrated fact sheet by Donald W. Hall and Jerry F. Butler, is part of the Featured Creatures collection. It describes this beautiful tiny blue butterfly that is locally common throughout peninsular Florida — its distribution, description, life cycle and biology, and hosts. Includes references. Published by the UF Department of Entomology and Nematology, June 2009.